2017
DOI: 10.1371/journal.pone.0170568
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Expression of Sox2, Gata3, and Prox1 during Primary Auditory Neuron Development in the Mammalian Cochlea

Abstract: Primary auditory neurons (PANs) connect cochlear sensory hair cells in the mammalian inner ear to cochlear nucleus neurons in the brainstem. PANs develop from neuroblasts delaminated from the proneurosensory domain of the otocyst and keep maturing until the onset of hearing after birth. There are two types of PANs: type I, which innervate the inner hair cells (IHCs), and type II, which innervate the outer hair cells (OHCs). Glial cells surrounding these neurons originate from neural crest cells and migrate to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 65 publications
8
52
0
Order By: Relevance
“…Previous studies had identified several genes that are expressed at different levels in mature type I and type II SGNs (Barclay et al, 2011; Hafidi, 1998; Lallemend et al, 2007; Mou et al, 1998; Nishimura et al, 2017; Vyas et al, 2017), and we have identified here many more. The functional consequences of these differences need to be explored, but one gene, Ngfr , provides an interesting example.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Previous studies had identified several genes that are expressed at different levels in mature type I and type II SGNs (Barclay et al, 2011; Hafidi, 1998; Lallemend et al, 2007; Mou et al, 1998; Nishimura et al, 2017; Vyas et al, 2017), and we have identified here many more. The functional consequences of these differences need to be explored, but one gene, Ngfr , provides an interesting example.…”
Section: Discussionmentioning
confidence: 63%
“…Mature type I SGNs can be distinguished from type II SGNs by high levels of Tubb3 expression while mature type II SGNs strongly express Prph (Barclay et al, 2011; Hafidi, 1998; Lallemend et al, 2007; Mou et al, 1998; Nishimura et al, 2017; Vyas et al, 2017). Unbiased clustering revealed groups of neurons that were separable on a t-Distributed Stochastic Neighbor Embedding (t-SNE) plot of all cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The identity of peripherin − , GFP + SGNs is uncertain. Recent work suggested that peripherin immunolabels only a subset of type II SGNs (Maison, Liberman, & Liberman, ; Nishimura, Noda, & Dabdoub, ; Vyas et al, ). Therefore, some of the peripherin − , GFP + SGNs are most likely type II afferent neurons.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the graded expression of Th and Cgrp α in type II SGNs, genetic tools based on them would affect only a subset of type II SGNs. A recent work suggested Gata3, a transcription factor that is expressed in all SGNs during development, could be a marker for type II SGNs in the adult cochlea (Nishimura et al, ). However, it remains to be determined whether Gata3 labels the entire type II neuron population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation